2020
DOI: 10.33314/jnhrc.v18i2.2244
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice on Family Planning among Married Muslim Women of Reproductive Age

Abstract: Background: Maternal mortality is associated with the unmet need of family planning. Family planning has been subjected as taboos in the Muslim community with low use of its methods. Gulariya Municipality is the second largest community for Muslim. This research focuses on knowledge, attitude and practice of family planning among Muslim women of reproductive age.Methods: Descriptive cross-sectional study design was undertaken in Gulariya Municipality. Married Muslim women of reproductive age group from 164 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
6
3
Order By: Relevance
“…However, this finding indicates poor practice compared to another study showing that 88% of women practice family planning in Al-Medina city [1], which is more than twice our findings, and 75.4% in Aseer [3]. Moreover, a study from Nepal found that most (79.3%) studied women were using family planning methods [26], which is twice the percentage we found. These differences could be attributed to the study's selection criteria, as the Al-Medina city study included teachers, 59.7% of whom were between the ages of 36 and 45, whereas the Abha City study included women of a higher age group, the majority of whom had been married for more than 11 years, implying that they used contraception earlier in their lives, as 53.5% had used contraception in the past.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…However, this finding indicates poor practice compared to another study showing that 88% of women practice family planning in Al-Medina city [1], which is more than twice our findings, and 75.4% in Aseer [3]. Moreover, a study from Nepal found that most (79.3%) studied women were using family planning methods [26], which is twice the percentage we found. These differences could be attributed to the study's selection criteria, as the Al-Medina city study included teachers, 59.7% of whom were between the ages of 36 and 45, whereas the Abha City study included women of a higher age group, the majority of whom had been married for more than 11 years, implying that they used contraception earlier in their lives, as 53.5% had used contraception in the past.…”
Section: Discussioncontrasting
confidence: 90%
“…In contrast, previous studies reported that the media, such as television, the internet, and newspapers, played an important role in increasing awareness of family planning [3,23]. On the other hand, some studies conducted in India, Nepal, and Ethiopia, showed that healthcare personnel was the main source of family planning information for women [16,[24][25][26]. Saudi cultural norms and the lack of a school curriculum teaching women about contraception could be the reason for sourcing information mainly from family and friends [27].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of this study is consistent with the study conducted in India [ 47 ]. However, previous studies in Nepal have reported no association between the type of family and knowledge of modern contraceptive methods [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 97%
“…For example, a previous study (2016) reported low (44%) knowledge on modern contraceptive methods among Muslim women in Nepal [ 34 ]. Another study showed relatively higher (94.5%) knowledge on modern contraceptive methods in Nepal [ 35 ]. About 87% of women knew contraceptive methods in India [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation